Origin of a counterintuitive yellow light-emitting electrochemical cell based on a blue-emitting heteroleptic copper(i) complex - Weber, Michael D; Garino, Claudio; Volpi, Giorgio; Casamassa, Enrico; Milanesio, Marco; Barolo, Claudia; Costa, Rubén D (Dalton transactions : an international journal of inorganic chemistry, 2016)
This work provides the synthesis, structural characterization, electrochemical and photophysical features, as well as the application in light-emitting electrochemical cells (LECs) of a novel heteroleptic copper(i) complex - [Cu(impy)(POP)][PF6], where impy is 3-(2-methoxyphenyl)-1-(pyridine-2-yl)imidazo[1,5-a]pyridine and POP is bis{2-(diphenylphosphanyl)phenyl}ether. This compound shows blue photoluminescence (PL, λ = 450 nm) in solution and solid-state and excellent redox stability. Despite these excellent features, the electroluminescence (EL) response is located at ∼550 nm. Although the EL spectrum of LECs is typically red-shifted compared to the PL of the electroluminescent material, a shift of ca. 100 nm represents the largest one reported in LECs. To date, the large shift phenomena have been attributed to (i) a change in the nature of the lowest emitting state due to a concentration effect of the films, (ii) a reversible substitution of the ligands due to the weak coordination to the Cu(i), and (iii) a change in the distribution of the excited states due to polarization effects. After having discarded these along with others like the irreversible degradation of the emitter during device fabrication and/or under operation conditions, driving conditions, active layer composition, and changes in the excited states under different external electrical stimuli, we attribute the origin of this unexpected shift to a lack of a thermally activated delayed fluorescence (TADF) process due to the solely ligand-centered character of the excited states. As such, the lack of a charge transfer character in the excited states leads to a blue-fluorescence and yellow-phosphorescence photo- and electro-responses, respectively. This corroborates recent studies focused on the design of TADF for heteroleptic copper(i) complexes. Overall, this work is a clear insight into the design of new copper(i) complexes towards the preparation of blue LECs, which are still unexplored.